2014
DOI: 10.1155/2014/691041
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Profiling of Schwann Cells in Contact with Growing Axons Distal to Nerve Injury

Abstract: Activated Schwann cells distal to nerve injury upregulate inflammatory mediators, including cytokines. The goal of the present study was to investigate expression of proinflammatory (IL-1β, TNFα) and anti-inflammatory cytokines (IL-4, IL-10) in activated Schwann cells in relation to growing axons distal to crush injury of rat sciatic nerves. Seven days from sciatic nerve crush, transverse cryostat sections were cut 5 mm distal to lesion and incubated for double immunostaining to indicate Schwann cells (GFAP or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 32 publications
(39 reference statements)
2
31
0
Order By: Relevance
“…Inflammation begins at the site of injury, and later involves the dorsal root ganglia (DRG), spinal cord and brain (Austin and Moalem-Taylor, 2010). Conventional immune cells such as mast cells, neutrophils, macrophages and T lymphocytes, along with other resident cells such as Schwann cells, microglia and astrocytes, exhibit activated profiles of gene expression producing a variety of inflammatory mediators that contribute to the initiation and maintenance of neuropathic pain (Austin and Moalem-Taylor, 2010; Dubovy et al, 2014; Ren and Dubner, 2010; Scholz and Woolf, 2007). Based upon previous studies, the cytokines that are consistently elevated in expression following peripheral nerve injury are TNF-α, IL-1β, and IL-6 (Sacerdote et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammation begins at the site of injury, and later involves the dorsal root ganglia (DRG), spinal cord and brain (Austin and Moalem-Taylor, 2010). Conventional immune cells such as mast cells, neutrophils, macrophages and T lymphocytes, along with other resident cells such as Schwann cells, microglia and astrocytes, exhibit activated profiles of gene expression producing a variety of inflammatory mediators that contribute to the initiation and maintenance of neuropathic pain (Austin and Moalem-Taylor, 2010; Dubovy et al, 2014; Ren and Dubner, 2010; Scholz and Woolf, 2007). Based upon previous studies, the cytokines that are consistently elevated in expression following peripheral nerve injury are TNF-α, IL-1β, and IL-6 (Sacerdote et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This axonal degeneration causes disorientation of the axon–Schwann cell organization, which initiates activation of the Schwann cells (Dubovy et al, 2014), as well as resident immune cells including mast cells, and macrophages. Activated Schwann cells as well as the immune cells secrete chemokines and cytokines that accelerate the recruitment of other immune cells from the bloodstream.…”
Section: Introductionmentioning
confidence: 99%
“…However, inappropriate inflammation (in time, place, and/or magnitude) is increasingly implicated in a wide range of pathologies [1]. This dual role of inflammation is also observed in the central nervous system (CNS), where neuroinflammation (NI) may take part in disease resolution [2] but also cause severe damage [3]. NI occurs when microglia, astrocytes (brain-resident cells), and perivascular macrophages at the blood-brain barrier (BBB) are activated.…”
Section: Introductionmentioning
confidence: 99%
“…Following injury, endogenous SCs present in the inflamed/injured nerve, including those in close contact with regrowing axons, upregulate a battery of proinflammatory cytokines and chemokines (Bolin et al ., ; Shamash et al ., ; Tofaris et al ., ; Martini et al ., ; Dubovy et al ., ). Given that we have now shown that SKPSCs express many of the same proinflammatory factors (Fig.…”
Section: Discussionmentioning
confidence: 97%